L’ECOLE, UN OUTIL D’URBANISATION EN CÔTE D’IVOIRE A TRAVERS LES CAS D’ABIDJAN ET DE YAMOUSSOUKRO - Kobenan Appoh Charles Bor; Atta Koffi Lazare; Gogbe Téré (European Scientific Journal, ESJ, 2013)
The school in the cities of Abidjan and Yamoussoukro, through schools and universities, has in recent years considerable changes both quantitatively and qualitatively. These changes have an impact at all levels, particularly in the urban dynamics of these cities. In Abidjan and Yamoussoukro, the school, through schools and universities, is one of several facilities that have a large spatial extent in the urban dynamics of these cities. Also, these schools and universities participate in change and habitat alteration in these cities. Therefore, the school is important equipment that contributes to habitat change and the urban landscape of the cities of Abidjan and Yamoussoukro. The school, through schools and universities, is presented as a precursor'' significant changes'' [Dhaher, N., 2009], the dynamics of urban development in the cities of Abidjan and Yamoussoukro.